2023
DOI: 10.1021/acsanm.2c05542
|View full text |Cite
|
Sign up to set email alerts
|

Femtomolar Level-Specific Detection of Lead Ions in Aqueous Environments, Using Aptamer-Derivatized Graphene Field-Effect Transistors

Abstract: The detection of lead ion (Pb2+) contamination in aqueous media is relevant for preventing endemic health issues as well as damage to cognitive and physical health. Existing home kit tests are unable to achieve clinically relevant sensitivity and specificity. Here, a label-free graphene field-effect transistor sensor for detecting Pb2+ at the femtomolar (fM) level, discriminating between confounding ions, is reported. The sensing principle is based on electrically monitoring Pb2+-binding-mediated conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Electronic sensors are potentially the most promising as they can simultaneously offer multiplexed, low-cost, high sensitivity detection with minimal human effort. Here, there is growing interest in graphene field effect transistors (GFET), which have shown the capability to detect everything from lead ions (Velusamy et al 2022; Dong et al 2023) to bacteria and oral disease biomarkers (Ping et al 2016b; Gao et al 2016; Kumar, Gray, et al 2020), though few have shown multiplexing capabilities (Lu et al 2022; Kumar et al 2022; Kumar, Gray, et al 2020). Nonetheless, only two groups, including ours, have demonstrated GFET’s use for detection of analytes in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic sensors are potentially the most promising as they can simultaneously offer multiplexed, low-cost, high sensitivity detection with minimal human effort. Here, there is growing interest in graphene field effect transistors (GFET), which have shown the capability to detect everything from lead ions (Velusamy et al 2022; Dong et al 2023) to bacteria and oral disease biomarkers (Ping et al 2016b; Gao et al 2016; Kumar, Gray, et al 2020), though few have shown multiplexing capabilities (Lu et al 2022; Kumar et al 2022; Kumar, Gray, et al 2020). Nonetheless, only two groups, including ours, have demonstrated GFET’s use for detection of analytes in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we hypothesize that extending the notion of surfaces to two-dimensional (2D) materials such as graphene or transition-metal dichalcogenides (TMDs), where the charge state could be tuned while retaining the aspect of hydrophobicity, could help in modulating the V s generation and related power conversion efficiency. We focus on the use of graphene based on extensive and prior reported work related to its electrical characteristics, structural and mechanical attributes, as well as the possibility of its deployment in applications, which could benefit from self-powered devices, e.g., pressure sensors, biosensors, flexible wearable devices, etc. Additionally, previous reports using graphene-based surfaces in micro-/nanofluidics, , with a focus on pressure-driven streaming flow and ionic concentration variations were also considered.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has the potential for such sensitive detection and has been applied to a wide variety of detection targets over the past 15 years, starting with the earliest research studies [30,31]. Such targets range from ions [32][33][34], gases [35][36][37], organic molecules [38,39], nucleic acids [40,41], and proteins [42] to viruses [43][44][45], bacteria [30,46], and cells [47,48]. The detection mechanisms of graphene biosensors are also diverse, including those based on electrical methods, such as those using field-effect transistors (FETs) [49,50] and electrochemical techniques [51][52][53], and optical methods, such as the use of molecular beacons [54,55], chemiluminescence assays [56,57], surface plasmon resonance spectroscopy [58,59], and Raman scattering spectroscopy [58,60].…”
Section: Introductionmentioning
confidence: 99%